Decision Support System for Palm Oil Collectors Selection at CV Afka Using Weighted Product - Silalahi, Antoni (Universitas Multi Data Palembang, 2024)
The selection of the right palm oil collectors is very important in the process of selling oil palm plantation products, because it can directly impact the sustainability of buying and selling between farmers and collectors. The main purpose of making this palm oil collector selection Decision Support System is to meet the needs of CV Afka in terms of selling its plantation products to collectors. The weighted product method is the main choice because it can accommodate various criteria relevant to the selection of palm oil collectors. This system is not only influenced by the price factor, but also by various other factors such as distance, road access, collector capacity, timeliness of payment, and service to farmers with the aim of understanding the specific needs and preferences of CV Afka in selecting palm oil collectors. Testing the decision-making system using the weighted product method is used to determine the decision to select palm oil collectors at CV Afka. The highest ranking result obtained from this test is alternative 8, namely Toke Sawit Raja Sobu with a preference value of 0.127.